Primary Teacher Working Group Assistance in the Indonesia-Malaysia Border Area to Design the Annual Work Program - Pebria D Purnasari; Totok Victor Didik Saputro; Silvester; Yosua Damas Sadewo (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Primary teacher working group assistance is one of the preparations for the teacher working group (KKG) in preparing the existing work program. The purpose of carrying out this activity is to carry out assistance to the SD teacher working group in designing an annual work program. The mentoring method used is the GROW Coaching Model approach which consists of 4 main stages, namely Grow, Reality, Options, and Will. The subjects of this activity were elementary school teachers in the Indonesia-Malaysia border region, especially in the KKG Group I Saka Taru environment, Lumar District, Bengkayang Regency, West Kalimantan. Mentoring activities are carried out by first delivering discussion material related to relevant activities as an example of an annual work program that can be carried out by the KKG Group I Saka Taru. The next stage is to make an annual work program roadmap and indicators of achievement in the implementation of the annual work program. This SD teacher working group assistance has produced an annual work program that is ready to be implemented one year ahead